CIA2 and CIA2‐LIKE are required for optimal photosynthesis and stress responses in Arabidopsis thaliana. (27th November 2020) - Gawroński, Piotr; Burdiak, Paweł; Scharff, Lars B.; Mielecki, Jakub; Górecka, Magdalena; Zaborowska, Magdalena; Leister, Dario; Waszczak, Cezary; Karpiński, Stanisław
SUMMARY: Chloroplast‐to‐nucleus retrograde signaling is essential for cell function, acclimation to fluctuating environmental conditions, plant growth and development. The vast majority of chloroplast proteins are nuclear‐encoded, and must be imported into the organelle after synthesis in the cytoplasm. This import is essential for the development of fully functional chloroplasts. On the other hand, functional chloroplasts act as sensors of environmental changes and can trigger acclimatory responses that influence nuclear gene expression. Signaling via mobile transcription factors (TFs) has been recently recognized as a way of communication between organelles and the nucleus. In this study, we performed a targeted reverse genetic screen to identify dual‐localized TFs involved in chloroplast retrograde signaling during stress responses. We found that CHLOROPLAST IMPORT APPARATUS 2 (CIA2) has a functional plastid transit peptide, and can be located both in chloroplasts and the nucleus. Further, we found that CIA2, along with its homolog CIA2‐like (CIL) are involved in the regulation of Arabidopsis responses to UV‐AB, high light and heat shock. Finally, our results suggest that both CIA2 and CIL are crucial for chloroplast translation. Our results contribute to a deeper understanding of signaling events in the chloroplast‐nucleus cross‐talk. Significance Statement: We found that a transcription factor CIA2 can be located in chloroplasts and nucleus and, together with its close homolog CIL, is involved in protein translation in the chloroplasts and abiotic stress responses.